A Comparative Analysis of Dynamic Interactions between European and Indonesian Cocoa Markets during the 2008 Global Financial Crisis and the 2011 European Debt Crisis - Mukhlis Mukhlis; M. Shabri Abd. Majid; Sofyan Syahnur; Musrizal Musrizal; Nova Nova (Comparative Economic Research. Central and Eastern Europe, 2021)
This study empirically explores the dynamic interactions between the European and Indonesian cocoa markets during the 2008 global financial crisis (GFC) and the 2011 European debt crisis (EDC) using a battery of time series approaches of cointegration and multivariate Granger causality. The study documented a long-run equilibrium between the European and Indonesian cocoa markets, implying a reciprocal relationship. However, an inefficient adjustment transmission in the Indonesian cocoa prices was recorded throughout the study. The US currency constantly influenced Indonesian cocoa prices, while cocoa markets were independent of fluctuations in world oil prices. Overall, the study recorded a different level of the speed of adjustment of short-run imbalances to long-run equilibrium in the domestic cocoa market across economic crises.
Keywords: C01; C23; O13; 330; cocoa market; CPI; exchange rate; oil price; economic crisis